AN OPINION SURVEY ON ISSUES OF PROVISION AND MANAGEMENT OF ADULT LITERACY PROGRAMME IN NIGERIA: IMPLICATIONS FOR PLANNING - Akinsolu, Abiodun Olatoun (Sokoto Educational Review, 2013)
There are almost 800 millions illiterate adults worldwide (UNESCO, 2005) Based on the above, there is an urgent need to expand the vision of both the MDGs to capture education for adult, so as to achieve the widespread agreement that through adult basic education and literacy intervention, human and social development can be enhanced (UNDP, 1997).This paper therefore examines issues in the provision and management o f adult literacy programme in Nigeria through a descriptive survey analysis o f ex- post facto. Guided by 4 Research questions and 1 hypothesis, findings revealed the perceptions o f beneficiaries in respect o f this programme. The paper concludes that the successful implementation o f adult literacy programme is the only way o f ensuring sustainable development in the country because it is only a man that can distinguish between truth and falsehood. He is really free to choose and participate actively in promoting socio. economic and political development o f his/her country while the planning implications were likewise highlighted.